EFFECTIVE UTILIZATION OF WASTES OF WOOD - Rozum , Rostyslav (Forestry, Forest, Paper and Woodworking Industry, 2009)
Basic directions of decision of important ecological problem of utilization of wastes of wood of enterprises of forestry, woodworking industry and agroindustrial complex are in-process considered. Possibilities of utilization of wastes of wood are analysed, as a perspective renewable energy source. In opinion of author the most effective method of utilization of arboreal wastes is making from them of fuel preforms. The analysed properties and application of fuel preforms domain are from wood. Comparative description of different types of fuel is resulted. It is set that the production of fuel preforms allows to decide the important ecological problem of utilization of wastes of wood of enterprises of forestry, woodworking industry and agroindustrial complex, and simultaneously to get additional environmentally clean and relatively cheap energoresursi.